Smart Payment Terminal in energy payment for electric and hybrid cars - Dankiewicz, Przemysław; Hernes, Marcin; Walaszczyk, Ewa; Tutak, Piotr; Chomiak-Orsa, Iwona; Rot, Artur; Kozina, Agata; Fojcik, Marcin; Dyvak, Mykola; Franczyk, Bogdan (Wykorzystanie urządzenia Smart Payment Terminal w realizacji płatności za energię przez użytkowników samochodów elektrycznych i hybrydowych, 2020)
One of the most important issues nowadays is reducing environmental pollution by decreasing car exhaust fumes. Increasing the customization of services forces companies to improve the selling process. One of the innovations used worldwide is the touchscreen in selfservice technology. The charging points for electric cars are often located in petrol stations so that the attendant carries out the payment process. However, there are more and more charging stations in other places, e.g. shopping centres, service stations, on-street parking, where there is no attendant. In such cases charging a car requires a mobile phone app for payment, and the app must be prepaid or have a connection to the customer’s bank account. There is no possibility to pay in cash or to receive an invoice.The aim of this paper is to present the Smart Payment Terminal (SPT) as an innovation in the energy-selling process for electric and hybrid cars in places with no attendant, and show its features and advantages. The paper has a R&D character. The main contribution is developing an innovative Smart Payment Terminal that allows payment with cash, credit cards, and fleet cards, and may print a receipt or an invoice directly after the purchase
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 111-126
Keywords: informatyka ekonomiczna